Comparative effectiveness of antitumour necrosis factor agents and vedolizumab in ulcerative colitis. Issue 6 (June 2019) - Davis, Rebecca; McParland, Paula; Dodd, Susanna; Storey, Daniel; Probert, Chris; Collins, Paul; Skouras, Thomas; Steel, Alan; Derbyshire, Edmund; Dibb, Martyn; Subramanian, Sreedhar
Abstract : Introduction: Antitumour necrosis factor (TNF) agents and vedolizumab are used to treat ulcerative colitis (UC) but the response is variable and there is little data on comparative effectiveness. Apart from previous exposure to anti-TNF agents, predictors of response have not been identified. We aimed to (i) compare the efficacy of anti-TNF agents and vedolizumab in UC and (ii) investigate the utility of clinical and biochemical parameters in predicting response. Patients and methods: Patients commencing any biological therapy for ambulant UC were included. Disease activity was monitored serially with the Simple Clinical Colitis Activity Index for up to 12 months. We compared the efficacy of anti-TNF agents and vedolizumab for induction and maintenance of response and remission on an intention-to-treat basis. We examined the utility of faecal calprotectin (FC) and early normalization of FC to predict response. Results: Ninety-seven patients commencing anti-TNF and 42 commencing vedolizumab therapy were included. Vedolizumab-treated patients had significantly greater previous anti-TNF therapy exposure and a lower baseline FC. Response, remission and steroid-free remission rates were comparable between both groups at 6 weeks, 6 and 12 months. Clinical remission but not steroid-free remission at 12 months was higher in the vedolizumab group. There was a significant reduction in the Simple Clinical Colitis Activity Index and FC at 6 weeks, 6 and 12 months compared with baseline in both groups. Baseline FC and early normalization did not predict response at 6 and 12 months. Conclusion: The efficacy of anti-TNF and vedolizumab in UC appear comparable. We could not identify any predictors of response and remission.